Arts based research - Barone, Tom, 1944-; Eisner, Elliot W. (Los Angeles Sage Publications, 2012)
"Arts Based Research is ideal for students, researchers, and practitioners. This unique book provides a framework for broadening the domain of qualitative inquiry in the social sciences by incorporating the arts as a means of better understanding and rethinking important social issues. In the book's 10 thought-provoking chapters, authors Tom Barone and Elliot W. Eisner--pioneers in the field--address key aspects of arts based research, including its purpose and fundamental ideas, controversies that surround the field and the politics and ethics involved, and key criteria for evaluation." -- Provided by publisher
Includes bibliographical references (pages 173-178) and index.
Keywords: Qualitative research -- Methodology; Arts and society; Electronic books